Libros de Cabildos de Lima.— Tomo XXI. (Años 1628-1630). Descifrado y Anotado por Juan Bromley.— Imp. Torres-Aguirre.—Lima 1963. (350 págs.) - Moreyra y Paz Soldán, Manuel (Revista Histórica, 2025)
Sin resumen.